Quick as a cricket - Wood, Audrey; Wood, Don, 1945- (New York, N.Y. : Child$1 (Bs Play (International),s, 1990)
A young boy describes himself as "loud as a lion," "quiet as a clam," "tough as a rhino," and "gentle as a lamb."
Keywords: Self-perception -- Fiction; Animals -- Fiction; Stories in rhyme